2015
DOI: 10.1021/acs.organomet.5b00926
|View full text |Cite
|
Sign up to set email alerts
|

Trifunctional pNHC, Imine, Pyridine Pincer-Type Iridium(III) Complexes: Synthetic, Structural, and Reactivity Studies

Abstract: Iridium­(III) complexes with a trifunctional pincer ligand containing protic N-heterocyclic carbene (pNHC), pyridine, and imine donor groups were obtained in two sequential steps: (i) protonation of 2-(1-(2,6-diiso­propyl­phenyl­imino)­ethyl)-6-(1-imidazolyl)­pyridine (L CH; the superscript specifies the position of the tautomerizable H atom in the imidazole ring) with HBF4·Et2O to give the imidazolium salt [HL CH]+[BF4]− (protonation always occurs at the imidazole N atom) and (ii) metalation of the latter wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The lower J Pt–P coupling constants measured for [ 5 ] + and [ 6 ] + are consistent with a decrease in electron density at the platinum center. Abstraction of a fluoride anion was confirmed by the appearance of new signals in the 19 F NMR spectrum at −134.7, −161.7, and −166.1 ppm and a broad singlet −191.4 ppm corresponding to the [BF­(C 6 F 5 ) 3 ] − anion . However, no signals corresponding to the antimony-bound fluoride ligands could be observed even at −50 °C in CDCl 3 .…”
Section: Resultsmentioning
confidence: 91%
“…The lower J Pt–P coupling constants measured for [ 5 ] + and [ 6 ] + are consistent with a decrease in electron density at the platinum center. Abstraction of a fluoride anion was confirmed by the appearance of new signals in the 19 F NMR spectrum at −134.7, −161.7, and −166.1 ppm and a broad singlet −191.4 ppm corresponding to the [BF­(C 6 F 5 ) 3 ] − anion . However, no signals corresponding to the antimony-bound fluoride ligands could be observed even at −50 °C in CDCl 3 .…”
Section: Resultsmentioning
confidence: 91%
“…In the absence of electrophilic reagents, the nucleophilic azolyl (or anionic NHC) complexes generated by deprotonation of pNHC ligands often dimerize to complexes of type 216 by replacement of one coligand, , as exemplified in Scheme …”
Section: Brønsted Acidity and Related Propertiesmentioning
confidence: 98%
“…During their studies on the chelate-assisted tautomerization of imidazole 81 bearing an imine–pyridine anchor, Danopoulos and Braunstein found that reaction of 81 with the iridium­(I) complex [IrCl­(cod)] 2 yields either the N-metalated iridium­(I)–imidazole complex 82 or the cyclometalated iridium­(III) complex 83 , depending on the ratio of metal precursor to 81 (Scheme ). If the imidazole moiety in 81 is protonated to give 84 , N-coordination of this group is suppressed, and oxidative addition to give the pincer-type pNHC iridium­(III) complex 85 was observed.…”
Section: Synthesismentioning
confidence: 99%
“…Different synthetic methodology led to the formation of the desired pincer ligand bound to Ir (25), and deprotonation of the NÀHt hen led to the homobimetallic Ir complex 26,d escribed as containing bridging imidazolide donors. [33] Ad ifferent synthetic methodr elied on the reactiono f2lithio-1-methylimidazole with au ranyl b-diketiminato chloride complex that led to ah eterobimetallic imidazolide complex with the Ca toms bound to Ua nd aL ic ation bridging between the Na toms (Scheme 5, 27). Upon reaction with CoCl 2 and FeCl 2 ,r earrangement was observed with the carbene C atom binding to the transition metal (TM, 28).…”
Section: No Linkermentioning
confidence: 99%